2004
DOI: 10.1111/j.1365-2966.2004.07313.x
|View full text |Cite
|
Sign up to set email alerts
|

BeppoSAX observations of 1-Jy BL Lacertae objects -- II

Abstract: We present new BeppoSAX LECS and MECS observations, covering the energy range 0.1–10 keV (observer's frame), of four BL Lacertae objects selected from the 1‐Jy sample. All sources display a flat (αx∼ 0.7) X‐ray spectrum, which we interpret as inverse Compton emission. One object shows evidence for a low‐energy steepening (Δαx∼ 0.9), which is probably due to the synchrotron component merging into the inverse Compton one around ∼2 keV. A variable synchrotron tail would explain why the ROSAT spectra of our source… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2005
2005
2007
2007

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 42 publications
1
18
0
1
Order By: Relevance
“…Data acquired by BeppoSAX on January 28, 1999 were reported by Padovani et al (2004). They found extra-absorption and both spectral index and flux consistent with the values derived by Madejski et al (1996) for the ASCA data.…”
Section: Previous X-ray Observations By Other Satellitessupporting
confidence: 66%
See 1 more Smart Citation
“…Data acquired by BeppoSAX on January 28, 1999 were reported by Padovani et al (2004). They found extra-absorption and both spectral index and flux consistent with the values derived by Madejski et al (1996) for the ASCA data.…”
Section: Previous X-ray Observations By Other Satellitessupporting
confidence: 66%
“…a (1) Worral & Wilkes (1990); (2) Ghosh & Soundararajaperumal (1995); (3) Madejski et al (1996); (4) Comastri et al (1997); (5) Webb et al (2000); (6) Junkkarinen et al (2004); (7) Padovani et al (2004). b F 2 keV .…”
Section: Introductionunclassified
“…As for the ROSAT spectrum, Madejski et al (1996) suggested that in a bright state the peak of the synchrotron component may shift to higher energies, and thus the synchrotron radiation would dominate in the soft X-ray region. This interpretation was also followed by Padovani et al (2004), when fitting the ROSAT spectrum with the homogeneous, one-zone model of Ghisellini et al (2002). However, this scenario is questioned by the contemporaneous optical data shown in Fig.…”
Section: Multiepoch Spectral Energy Distributionmentioning
confidence: 75%
“…also [5]). A rough order-of-magnitude estimate for the physical parameters in the emitting region may be obtained by fitting the multiwavelength SED with a homogeneous, one-zone synchrotron -inverse Compton model, suggesting viewing angles ∼ 2.9 • , magnetic field strengths ∼ 3.8 Gauss and bulk Lorentz factors ∼ 16 for the low state ( [28]). The analysis of the long-term variability in AO 0235+16 over a time range of ∼ 25 yr has revealed evidence for a (5.7 ± 0.5) yr periodicity in its radio lightcurves and a possible (2.95 ± 0.15) yr periodicity in its optical lightcurves, e.g.…”
Section: Application To Ao 0235+16mentioning
confidence: 99%